2013
DOI: 10.1371/journal.pone.0073133
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Liver-Specific miR-122 as a Novel Potential Biomarker for Diagnosis of Cholestatic Liver Injury

Abstract: BackgroundCirculating microRNA-122 (miR-122) has been increasingly reported to be a potential biomarker for drug-, viral-, alcohol- and chemical-induced liver injury. The present study was initiated to determine the potential of circulating miR-122 as a biomarker for cholestatic liver injury.MethodsBoth bile-duct ligation (BDL) mice and patients with biliary calculi were employed as cholestatic liver injury models, and serum miR-122 level was determined by stem-loop real-time reverse-transcription PCR (SLqRT-P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 28 publications
5
30
0
Order By: Relevance
“…In this study, we found that patients with severe acute viral hepatitis, who displayed high ALT, AST and bilirubin levels as well as an abnormal prothrombin time, showed significantly higher serum levels of mir‐122 than patients with moderate hepatitis. These data are in accordance with previous findings and confirm that the mir‐122 serum level might reflect the inflammatory activity and the amount of injury in the liver . Our data also correspond to recent findings from John et al .…”
Section: Discussionsupporting
confidence: 93%
“…In this study, we found that patients with severe acute viral hepatitis, who displayed high ALT, AST and bilirubin levels as well as an abnormal prothrombin time, showed significantly higher serum levels of mir‐122 than patients with moderate hepatitis. These data are in accordance with previous findings and confirm that the mir‐122 serum level might reflect the inflammatory activity and the amount of injury in the liver . Our data also correspond to recent findings from John et al .…”
Section: Discussionsupporting
confidence: 93%
“…Serum levels of miR-122-5p were increased, while the expression of miR-122-5p was reduced in liver tissue, which could be due to passive miRNA drainage from tumour cells, as has been observed in other tumours [123]. Expression of miR-122-5p has been identified as a non-specific marker of liver damage, and is increased in the serum of jaundiced patients [124]. These studies highlight the importance of identifying miRNA profiles (in tumour tissue and in serum), and shows that there may be specific miRNAs with unique roles in various types of childhood solid tumours.…”
Section: Introductionmentioning
confidence: 97%
“…Currently, alanine transaminase (ALT), also known as the serum glutamic‐pyruvic transaminase, is the predominant hepatocyte enzyme that is routinely used to detect liver injury . Another novel biomarker that was recently used to detect liver injury is miRNA‐122 (miR‐122) . miRNA (miR), a single‐stranded RNA, regulates the functions of mRNA including the interference of post‐translational gene regulation procedures such as the degradation of the mRNA and the blockade of the translation processes .…”
Section: Introductionmentioning
confidence: 99%
“…miR‐122 is abundantly expressed on hepatocytes and responsible for several hepatic‐involved pathways such as the liver lipid metabolism, hepatitis C amplification and interferon antiviral responses, hepatocellular carcinoma development and hepatocyte apoptosis . Circulating miR‐122 is a sensitive biomarker that can be used to detect early hepatic injury from several causes such as drugs, alcohol, bile salts, chemical substances and viruses . Recently, circulating miR‐122 was tested in a human pilot study for detecting liver damage .…”
Section: Introductionmentioning
confidence: 99%